Potencial da Escallonia bifida Link & Otto (Escalloniaceae) para utilização em ações de restauração ecológica no Rio Grande do Sul - Felker, Roselene Marostega (2014)
This paper presents the study of Escallonia bifida Link & Otto, a native species of the Deciduous Forest Biome feature of the Atlantic Forest, which has characteristics of a pioneer, great hardiness. This study aimed to evaluate its potential as an alternative species in restoration activities in their region of origin, as well as increase knowledge of the species, very little studied so far, defining characteristics and generating useful information for their use in restoration plans. The study was conducted in Deciduous Forest Atlantic, Biome fragment, located in the protected State Park Quarta Colônia, central region of Rio Grande do Sul. For better structuring and understanding, the work was divided intofour chapters, covering morphological and ecological description of species Escallonia bifida, the same population structure, the relationship between species and environmental variables and their importance in shaping floristic groups for the tree stratum. Chapter I deals with the morphological characterization of the species Escallonia bifida for the state of Rio Grande do Sul, through the description of leaf structures, flowering, fruiting, and a brief bibliographic description about it. Chapter II presents a study on the population structure of Escallonia bifida, main phytosociological parameters as well as their spatial distribution in the area, compared to other species occurring in the studied fragment. Chapter III discusses the relationship between Escallonia bifida and environmental variables. Chapter IV addresses the tree stratum, where floristic groups formed in the area, compared with environmental variables, as well as the importance of Escallonia bifida in the definition of floristic groups present in the study area were defined. In general, it can be seen that the species has potential for use in restoration activities in the study area due to its hardiness and colonization of open areas. Moreover, it is observed that in the tree layer species can be found in the pioneering groups of early secondary, which acts as an indicator species. The species also has multiple potential of afforestation, honey production and as an alternative to restoration projects. In this sense, it will be of great importance to the maintenance and expansion of studies with this species in order to deepen knowledge, since there is little literature on the same.